Information Technology in Electronic Land Registration System as the Standard of Government Performance in the Industry 4.0 Revolution - Handoko, Widhi; Yubaidi, Ricco Survival (APPTHI, 2020)
Land law policy covers fundamental aspects, namely the principle of fulfilling the people’s constitutional rights to meet daily life’s needs and respect the principle of human equality. One of the objectives of the establishment of the Republic of Indonesia, as mandated by the 1945 Constitution, is to realize public welfare. The government’s main task is to create a government management system that can properly manage national resources to achieve prosperity and prosperity and social justice for all the people of Indonesia. The government must be able to realize land law reform, especially public services in the land sector. The formation of the National Bureaucracy Reform Committee is aimed at continuing the government’s plans that have not been effective, namely the creation of an accountable, productive, professional, and free of corruption bureaucracy. The most important improvement effort on land law reform is to reconstruct the land registration system in realizing the industrial revolution 4.0, in the form of an electronic certificate on land as a form of creativity and innovation to grow and develop digital technology while forming a legal culture in bureaucratic services and strong public services. Abstrak Kebijaksanaan hukum pertanahan mencakup aspek-aspek mendasar, yaitu asas pemenuhan hak konstitusional rakyat untuk memenuhi kebutuhan hidup sehari-hari dan menjunjung tinggi asas persamaan hak asasi manusia. Salah satu tujuan berdirinya Negara Republik Indonesia sebagaimana diamanatkan oleh UUD 1945 adalah untuk mewujudkan kesejahteraan umum. Tugas pokok pemerintah adalah mewujudkan sistem penyelenggaraan pemerintahan yang dapat mengelola sumber daya nasional dengan baik untuk tercapainya kemakmuran dan kesejahteraan serta keadilan sosial bagi seluruh rakyat Indonesia. Pemerintah harus mampu mewujudkan reformasi hukum pertanahan, khususnya pelayanan publik di bidang pertanahan. Pembentukan Komite Reformasi Birokrasi Nasional bertujuan untuk melanjutkan rencana pemerintah yang belum efektif, yaitu mewujudkan birokrasi yang akuntabel, produktif, profesional dan bebas korupsi. Upaya pembenahan reformasi hukum pertanahan yang terpenting adalah merekonstruksi sistem pendaftaran tanah dalam mewujudkan revolusi industri 4.0, berupa sertifikat tanah elektronik sebagai bentuk kreativitas dan inovasi menumbuhkan dan mengembangkan teknologi digital, sekaligus membentuk budaya hukum. dalam pelayanan birokrasi dan pelayanan publik yang kuat. Kata kunci: Teknologi informasi, Sistem registrasi elektronik, Land reform, Revolusi industri 4.0